(3v-1)(5+v)=0

Simple and best practice solution for (3v-1)(5+v)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3v-1)(5+v)=0 equation:


Simplifying
(3v + -1)(5 + v) = 0

Reorder the terms:
(-1 + 3v)(5 + v) = 0

Multiply (-1 + 3v) * (5 + v)
(-1(5 + v) + 3v * (5 + v)) = 0
((5 * -1 + v * -1) + 3v * (5 + v)) = 0
((-5 + -1v) + 3v * (5 + v)) = 0
(-5 + -1v + (5 * 3v + v * 3v)) = 0
(-5 + -1v + (15v + 3v2)) = 0

Combine like terms: -1v + 15v = 14v
(-5 + 14v + 3v2) = 0

Solving
-5 + 14v + 3v2 = 0

Solving for variable 'v'.

Factor a trinomial.
(-5 + -1v)(1 + -3v) = 0

Subproblem 1

Set the factor '(-5 + -1v)' equal to zero and attempt to solve: Simplifying -5 + -1v = 0 Solving -5 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1v = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1v = 0 + 5 -1v = 0 + 5 Combine like terms: 0 + 5 = 5 -1v = 5 Divide each side by '-1'. v = -5 Simplifying v = -5

Subproblem 2

Set the factor '(1 + -3v)' equal to zero and attempt to solve: Simplifying 1 + -3v = 0 Solving 1 + -3v = 0 Move all terms containing v to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3v = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3v = 0 + -1 -3v = 0 + -1 Combine like terms: 0 + -1 = -1 -3v = -1 Divide each side by '-3'. v = 0.3333333333 Simplifying v = 0.3333333333

Solution

v = {-5, 0.3333333333}

See similar equations:

| 3x^2+34x=440 | | 4a-7=a-5 | | 21x-15x-7=5 | | (7x/8)-(x-2)=12 | | -36+324= | | (1-6x+2u)(-3)= | | 0.15*0.23= | | 7x+8+5x+2+7x-1=180 | | -11x+x^2=-2+30 | | 8.2=2x-4 | | -5(-5x-v+6)= | | y=25(3)+200 | | 4n-3=16 | | 0.27*0.56= | | y=25(3)-200 | | 4h-7g+11g-h= | | 12-3x=4+(-4x) | | x^2-11x+214=0 | | (5x+4)+(4d+5)= | | 4K-5=2k-1 | | 8x-20=64 | | http://www.thelearningodyssey.com/Assess/DPT/QIEImagesStorage/AQ13A/AQ13AI_A1322_14_stem1_1.gif | | 7a-4=4(3a+1) | | 1+(P-1)=5(P+6) | | -7x-117=12x+130 | | -9-2m-m=8m-9 | | 16x^2-40x+100=0 | | x^2-10x+16=o | | X^4+14x^2-49=0 | | -9x-15=-8x+11 | | -(3u-2x-3)= | | t/8-8=8 |

Equations solver categories